Does herding behavior exist in cryptocurrency market? - Amina Amirat; Wafa Alwafi (Cogent Economics & Finance, 2020)
This paper investigates the existence of herding behavior in cryptocurrencies market. Using data of the 20 large cryptocurrencies and MV Index Solution Crypto Compare Digital Assets for large cap index, we found no evidence of herding behavior using cross-sectional absolute standard deviation estimation. However, by applying a rolling window analysis, the results show significant herding behavior, which varies over time. Finally, we find an inverse relationship between herding behavior and the Bloomberg consumer comfort index which means that when traders are less comfortable they prefer to ignore their expectations and follow the market performance.
Keywords: G12; G14; G40; 330; cryptocurrency; CSAD; herding behavior